Expenditure on Fadama User Groups’ Sub-Projects and Fadama Community Associations; Comparative Appraisal in Rivers State, Nigeria - Neeka Igbara; Abraham Anthony (Research Parks Publishers, 2021)
The implementation of Fadama III programme in Rivers State was in line with World Bank laid down criteria which operated successfully through two major platforms; Fadama User Group and Fadama Corporative Association in achieving maximum objectives. This paper conducted a comparative appraisal of expenditure on Fadama III User Groups’ Sub-Projects and Fadama Corporative Associations’ in Rivers State, Nigeria. The study was limited to the period of five years; 23rd March, 2009 to 31st December, 2013 that Fadama third phase lasted. Information was sourced through secondary materials. Descriptive Statistics of tables, frequencies, percentages, Pie and Bar charts were used in the analysis. Findings revealed that seven out of the twenty-three local government areas in Rivers State did not participate in the programme due to their inability to pay counterpart funds and provide desk offices in their local government councils. Therefore, farmers could not organize themselves into Fadama User Groups (FUGs) and Fadama Cooperative Association (FCAs). The programme performed better as funds were prudently managed in pro-rata approach to accommodate numerous demands from groups that met Fadama criteria. Benefiting communities got quality agricultural productivity aiding infrastructure through Fadama programme. The study recommended that the duration of Fadama programme should be extended and more funds released for increased provision of rural infrastructure